2012
DOI: 10.1007/s10286-012-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms of neurological origin in urological practice

Abstract: Consideration of detailed medical history, enforcement of UDS, and closer cooperation between urologists and neurologists are required to ascertain early and correct diagnosis, and to avoid unnecessary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…A detailed assessment of LUT dysfunction is important to underpin diagnosis of MSA as well as to anticipate potential coexisting conditions and thus, to avoid unnecessary surgeries. 45 It is important to note, that in contrast to Parkinson's disease, benign prostatic hypertrophy (BPH) surgery worsens bladder function and is contraindicated in MSA patients. 19 In the following study we have demonstrated that surgery due to prostate hypertrophy worsened bladder function in MSA in 7 of 10 patients and did not improve bladder function considerably in the remaining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed assessment of LUT dysfunction is important to underpin diagnosis of MSA as well as to anticipate potential coexisting conditions and thus, to avoid unnecessary surgeries. 45 It is important to note, that in contrast to Parkinson's disease, benign prostatic hypertrophy (BPH) surgery worsens bladder function and is contraindicated in MSA patients. 19 In the following study we have demonstrated that surgery due to prostate hypertrophy worsened bladder function in MSA in 7 of 10 patients and did not improve bladder function considerably in the remaining.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results emphasize that besides the application of clinical criteria, neuro‐urological and urodynamic examination may be indispensable in a subset of patients. A detailed assessment of LUT dysfunction is important to underpin diagnosis of MSA as well as to anticipate potential coexisting conditions and thus, to avoid unnecessary surgeries 45 . It is important to note, that in contrast to Parkinson's disease, benign prostatic hypertrophy (BPH) surgery worsens bladder function and is contraindicated in MSA patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Вже було опубліковано, що УДД у багатьох випадках суттєво змінювало клінічне враження лікаря стосовно діагнозу пацієнта, пов'язаного зі стресовим нетриманням сечі та невідкладним нетриманням сечі [2]. УДД також може допомогти в кращому розумінні дисфункцій у пацієнтів із неврологічними розладами, а також у розумінні змін функцій нижніх сечовивідних шляхів у пацієнтів з онкологічними захворюваннями гінекологічних органів малого таза до та після радикального лікування [3,4]. УДД -це інвазивна процедура, яка передбачає катетеризацію; тому після проведення УДД можуть спостерігатися інфекції сечовивідних шляхів (ІСШ) або бактеріурія, причому частота бактеріурії становить від 1,5% до 30% [5].…”
Section: в п о м о щ ь п р а к т и ч е с к о м у в р а ч уunclassified
“…It has been already published that UDS, in many cases, significantly changed the ordering clinician's clinical impression of the patient's diagnosis for stress urinary incontinence and for urgency urinary incontinence [ 2 ]. UDS can also help in the better understanding of dysfunctions in patients with neurologic disorders, and in comprehending the changes in lower urinary tract functions in patients with pelvic gynaecologic cancer before and after radical treatment [ 3 , 4 ]. UDS are an invasive procedure that involves catheterization; therefore, urinary tract infection (UTI) or bacteriuria may be observed after UDS, with an incidence of bacteriuria ranging from 1.5 to 30% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%